Invitro Biodegradability of Silk Fibroin/Xanthan Biopolymeric Composite Scaffolds - Shera S.S.; Sahu S.; Banik R.M. (My University, 2025)
Silk fibroin/xanthan scaffolds were prepared by blending silk fibroin and xanthan in the ratios 80SF:20Xa (SFX82), 60SF:40Xa (SFX64), and 50SF:50Xa (SFX55) using freeze drying method. In-vitro degradation behavior of the prepared scaffolds was studied for 37 days in phosphate buffer saline. The degradation rate was the function of silk fibroin, xanthan and β-crystallite contents in the silk fibroin/ xanthan composites. SFX82 degraded extremely slowly whereas SFX55 showed faster degradation rate. Hydrophilic xanthan was the main contributor of weight loss. SFX82 and SFX64 exhibited surface degradation whereas SFX55 showed bulk degradation which indicated that higher silk fibroin ratios favor surface degradation. Due to bulk degradation, SFX55 showed maximum surface roughness among the composite scaffolds. The FTIR spectrum revealed total loss of xanthan from the composites after degradation. The broad and low-intensity peaks in the FTIR spectrum of composite scaffolds confirmed reduction in β-sheet crystallite content during degradation. XRD analysis also confirmed reduction in β-sheet crystals and revealed that degraded composite scaffold had predominantly amorphous structure. The degraded scaffold showed higher porous structure than the non-degraded scaffold. The in vitro degradability testing gives a good approximation of degradation of scaffold in vivo and helps in designing a robust biopolymeric composite scaffold for tissue engineering. © 2019, Jilin University.